Aspekty metodyczne prognozowania cen światowych dla potrzeb krajów RWPG - Janc, Alfred (Wydział Prawa i Administracji UAM, 1981)
In the process of — widely understood — using would market pirices for the needs of the CMEA, several stages can be distinguished. Effectiveness of the whole process is determined by realization of those stages. Following stages should be marked off: (1) approval — by the CMEA countries — of using world market prices in definite spheres of mutual co-operation; (2) choice of organizational forms of forecasting world market prices within the CMEA; (3) selection of methods and techniques of foreassting, adequate for a given commodity and for certain sphere of co-operation; (4) realization of the foreassting process and forecasts verification; (5) introduction of forecasts to mutual enterprises undertaken by the CMEA-countries in the sphere of production and trade. The author occupies himself with methodical aspects of forecasting world markest prices. There fundamental groups can be distinguished among method, of world market prices forecasting. Econometric methods consist in broad utilizetion of mathematical, statistical and econometric techniques in price models construction. A world price forecast can also be obtained owing to non-econometric methods. Those ones are based on knowledge of experts and its using for forecasting purposes. The usability, however, of the mixed method of forecasting. should be seen in analytic activities concerning world prices. The method in question should combine both non-econometric methods and technique and econometric ones. Utilization of a mixed methodical variant enables a more comprehensive reflection and analysis of factors influencing the prices as well as the most precise reflection of that influence. Furthermore, the influence of verification procedures on prices accepted within the CMEA is discussed as well as instruments of verifications of forecasts results are analyzed. The problem can be of some importance in case of forecasts utilization within the CMEA. In its final part the article contains considerations on problems of forecasts horizon and data modernization. It is analyzed in connection with the problem of reliability of forecasts results used within the grouping.
Methodical Aspects of Forecasting World Market Prices for the Needs of the Council for Mutual Economic Aid